Income and Wealth Inequality in America, 1949-2013 - Moritz Kuhn; Moritz Schularick; Ulrike I. Steins (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies the distribution of U.S. household income and wealth over the past seven decades. We introduce a newly compiled household-level dataset based on archival data from historical waves of the Survey of Consumer Finances (SCF). Complementing recent work on top income and wealth shares, the long-run survey data give a granular picture of trends in the bottom 90% of the population. The new data confirm a substantial widening of income and wealth disparities since the 1970s. We show that the main loser of rising income and wealth concentration at the top was the American middle class – households between the 25th and 75th percentile of the distribution. The household data also reveal that the paths of income and wealth inequality deviated substantially. Differences in the composition of household portfolios along the wealth distribution explain this divergence. While incomes stagnated, the middle class enjoyed substantial gains in housing wealth from highly concentrated and leveraged portfolios, mitigating wealth concentration at the top. The housing bust of 2007 put an end to this counterbalancing effect and triggered the largest spike in wealth inequality in postwar history. Our findings highlight the importance of portfolio composition, leverage and asset prices for wealth dynamics in postwar America.
Keywords: D31; E21; E44; N32; 330; income and wealth inequality; household portfolios; historical micro data